Efektivitas Penggunaan Media Wordwall Dalam Latihan Harian Matematika Materi Denah dan Skala Terhadap Hasil Belajar Siswa di SDN Menteng 03 - Firqy Indriyani; Tiurlina; Fitri Alfarisa (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2022)
Researchers aim to see the effectiveness of wordwall media usage and the student responsesto wordwall media. According to the results of the interview at SDN menteng 03, during thecovid-19 pandemic the study was conducted online. Daily exercises performed during onlinestudy of mathematics at SDN menteng 03 are still in the way teachers give the problems andstudents copy them into the textbook afterward in photos and then are sent personally through the whatsapp to the subject teacher. The teacher has not used a medium that can be used in daily practice. The method used is the quantitative approach using a pre-design design design for one - group preafflicted posttest design that is a pre-experiment study that USES one group but there are pretests and posttests (yuwanto listyo, 2019:153). According to the data the pretest of the student is 66.56 and the student posttest is 88.75. According to nurgana (within nurhadi, 2018:109) learning can be categorized effectively, if 75% of students get a higher value or equal to KKM ata value of 70. In turn, wilcoxon tests are designed to learn more about the effectiveness of the use of the wordwall media, with its significant value of 0,000 or 0,0000.05, and ho has been rejected, which suggests an average difference between the study of mathematics for pretest and posttest so that it can be proved that the use of wordwall media is effective in mathematical daily exercise activities on grid and scale materials. Research has been continuing to learn how students respond to media use with a student's response to wordwall media usage falls under a "high" category with a frequency of 16 students or 50% of the class student population v SDN menteng 03. Thus, from the data it is known that students have a good response to the use of wordwall media in daily exercise activities.